1995
DOI: 10.1155/s0161171295000731
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic‐gravity waves in a viscous and thermally conducting isothermal atmosphere (part II: For small Prandtl number)

Abstract: In part one of these series we investigated the effect of Newtonian cooling on acoustic-gravity waves in an isothermal atmosphere for large Prandtl number. It was shown that the atmosphere can be divided into two regions connected by an absorbing and reflecting layer, created by the exponential increase of the kinematic viscosity with height, and if Newtonian cooling coefficient goes to infinity the temperature perturbation associated with the wave will be eliminated. In addition all linear relations among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Consequently, there are four linearly independent solutions, which in the neighborhood of 0 can be written in the following form TI() E an (el),n+.,, T2 () E aS (e2)"+e' + T1 ()log(), T3() E an(e3)"+e" T4() E a, (e4) '+e + T3()log(), (4 5) where el 2, e2 1, e3 e4 0 The prime denotes differentiation of a, and the sums are taken from n 0 to n oo. The coefficients o(e,) are determined from the following three term recursion formula po(n + 2 + e)an+2 + Pl (n + 1 + e)an+l + p2(n + e)an 0, (4.6) Following the same procedure as in Part II (Alkahby [9]), the solution of the differential equation, which satisfies the prescribed boundary conditions can be written in the following form T(z) clTI(z) + c2T3(z). (4 $) To determine the linear combination of T(z) in equation (4.8), the behavior ofT1 (z) and T3(z) for small z must be found Since small z corresponds to large ](] with arg()= 3r/2 + O,, the asymptotic expansions ofT1 () and T3() about infinity should be found.…”
Section: The Effect Of Newtonian Cooling Alonementioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, there are four linearly independent solutions, which in the neighborhood of 0 can be written in the following form TI() E an (el),n+.,, T2 () E aS (e2)"+e' + T1 ()log(), T3() E an(e3)"+e" T4() E a, (e4) '+e + T3()log(), (4 5) where el 2, e2 1, e3 e4 0 The prime denotes differentiation of a, and the sums are taken from n 0 to n oo. The coefficients o(e,) are determined from the following three term recursion formula po(n + 2 + e)an+2 + Pl (n + 1 + e)an+l + p2(n + e)an 0, (4.6) Following the same procedure as in Part II (Alkahby [9]), the solution of the differential equation, which satisfies the prescribed boundary conditions can be written in the following form T(z) clTI(z) + c2T3(z). (4 $) To determine the linear combination of T(z) in equation (4.8), the behavior ofT1 (z) and T3(z) for small z must be found Since small z corresponds to large ](] with arg()= 3r/2 + O,, the asymptotic expansions ofT1 () and T3() about infinity should be found.…”
Section: The Effect Of Newtonian Cooling Alonementioning
confidence: 99%
“…[IV] It follows from [III] and the results, which were obtained in Alkahby [8,9], that the effect of thermal conduction on the reflection and dissipation of the wave will be eliminated if the heat exchange between the hotter and cooler region in the atmosphere is intense and the oscillatory process is transformed from the adiabatic form to the isothermal one.…”
Section: The Effect Of Newtonian Cooling Alonementioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, some similar studies took into consideration a horizontal magnetic field (e.g., [30][31][32]). Particularly, in a series of work on the combined effect of Newtonian cooling, viscosity and thermal conduction, Alkahby [33][34][35] demonstrated that, for an arbitrary value of the Newtonian cooling coefficient, on the one hand, a large Prandtl number divides an atmosphere into two distinct regions between which there is an absorbing and reflecting layer produced by the exponential increase of the kinematic viscosity; on the other hand, a small Prandtl number divides the atmosphere into three distinct regions when the Newtonian cooling coefficient is small, while the two lower regions merge into one if the Newtonian cooling coefficient is large. For an arbitrary Prandtl number, it was found that the effect of the thermal conduction is dominated by that of the viscosity if the Newtonian cooling coefficient is small and becomes eliminated completely if the Newtonian cooling is large.…”
Section: Introductionmentioning
confidence: 99%